Metabolic Syndrome and Insulin Resistance in Schoolchildren From a Developing Country - Das, Rashmi Ranjan; Mangaraj, Manaswini; Panigrahi, Sandeep Kumar; Satapathy, Amit Kumar; Mahapatro, Samarendra; Ray, Partha Sarathi (Frontiers in Nutrition, 2020)
Background: Childhood overweight and obesity is prevalent in school going children due to dietary habits and lack of exercise. These children are prone for metabolic syndrome (MS) and future risk of type 2 diabetes mellitus and cardiovascular diseases. Materials & Methods: This school-based cross-sectional study was conducted in Bhubaneswar city, Eastern India among school going children. Obesity and overweight were determined by Indian Academy of Pediatrics (IAP) guideline. Fasting venous blood samples were taken for insulin, blood sugar, and lipid levels measurement. BP was measured as per the protocol. The International Diabetic Federation (IDF) criteria for definition of MS were followed. Insulin resistance was determined by a homeostatic model assessment (HOMA-IR). Results: A total of 1930 children were screened, of which 545 (28.2%) were overweight & obese. The male to female ratio was 1.27. The prevalence of MS among overweight/obese children from 6 to ≤10 year was 11%, and from 11 to 16 year was 30.6%. The overall prevalence of MS in overweight/obese was 21.8%. History of cardiovascular disease, diabetes, obesity and hypertension in family were present in 42.7%. Acanthosis nigricans was present in 46.4%. History of exclusive breast feeding for 6 months was present in 68.1%. The mean HOMA-IR in children with MS was 5.46 compared to 2.18 in those without MS. This means, the insulin resistance was commoner in children with MS. Conclusions: The present study found a higher prevalence of MS and insulin resistance in overweight & obesity school going children from Eastern India.